ANALISIS SISTEM PEMBELAJARAN SLB SAMUDRA LAVENDER BANGKALAN DALAM UPAYA MENGEMBANGKAN FUNGSI SOSIALISASI DAN POTENSI SISWA BERKEBUTUHAN KHUSUS - AMELIA, NANDA; FAUZIAH, NUR ROCHMAH ANGGUN; SETYAWAN, AGUNG (Pusat Riset dan Inovasi Nasional, 2022)
This article describes the results of research related to the learning system carried out at SLB Samudra Lavender, Bangkalan and using qualitative methods. The purpose of this study is to describe how the learning system takes place in order to improve the development of the socialization function and the potential of students in the school. Researchers took the SLB Samudra Lavemder, Bangkalan as the object of research. Data collection was carried out by interviewing the principal at SLB Samudra Lavender, Bangkalan as well as direct observations by researchers which would later be proven through documentation. The schools that the researchers observed made various efforts to develop the development of the socialization function and potential in students at the school by analyzing the applied learning system. Many people in general often underestimate the ability of children with special needs, therefore the researcher wants to find out more about the efforts made by educators in one of the special schools in one of the schools in Bangkalan district. The obstacles experienced by the teacher during the learning process are the difficulties of the students to comply with what the educator wants or says so that the class becomes crowded and learning becomes not conducive. In addition, there is a miscommunication between educators and parents of students so that there is no close relationship to compromise on the development of students from within. Various efforts have been made by educators so that it is not uncommon for SLB Samudra Lavender to get awards in various activities such as exhibitions.